Colletotrichum isolates related to Anthracnose of cashew trees in Brazil: morphological and molecular description using LSU rDNA sequences - Lopez,Ana Maria Queijeiro (2010)
Thirty six isolates of fungi obtained from anthracnose lesions of cashew and associated host plants in Brazil, were compared by their cultural, morphological and partial sequences of the 28S ribosomal DNA characters. They showed a high degree of cultural variability. The average mycelial growth rate on all tested media ranged from 10.2-13.3 mm/day between the isolates. Most of them produced perithecia (sterile and fertile) and some produced setae (sterile and fertile). All the isolates produced acervuli with predominantly cylindrical conidia (12.4-17.7 µmX 4.8-6.0 µm in width) with round ends, which became septate on germination, and produced unlobed or slightlylobed appressoria. Comparison of the D2 domain of the large subunit (LSU) rDNA sequences with those of other defined species of Colletotrichum and Glomerella grouped 35 of the isolates with known strains of C. gloeosporioides from different hosts (> 98.9% homology). The one exception (LARS 921) was identical to G. cingulata (LARS 238) from Vigna unguiculata.